Guru Profesional Di Era Digital - Mukmin; Nur Nafisatul Fithriyah; Habib Zainuri; Muhammad Naufal Ghazali (JIEES : Journal of Islamic Education at Elementary School, 2023)
Being a professional teacher in the digital era presents a significant challenge as students have a greater understanding of technology. To keep up with students' development, teachers need to continuously enhance their knowledge, skills, and understanding in digital platforms. While some teachers are familiar with technology, others may struggle with its use, leading to them being considered outdated. However, the digital era has made it easier for teachers to convey their lessons through various methods, especially in digital media. A recent study utilized literature review and content analysis to explore the changes that professional teachers need to make in the digital era. The results suggest that teachers must adapt to the digital era without compromising their professionalism. The study emphasizes the need for teachers to gain mastery in understanding the digital era in order to stay informed and keep pace with the rapidly changing times.